2023
DOI: 10.2147/jir.s396321
|View full text |Cite
|
Sign up to set email alerts
|

Association of Enolase-1 with Prognosis and Immune Infiltration in Breast Cancer by Clinical Stage

Abstract: Purpose Enolase-1 (ENO1) plays a key role in malignancies. Previous studies on the association between ENO1 expression and breast cancer prognosis had yielded inconsistent results. In the present study, we assessed the prognostic effect of ENO1 in breast cancer using Guangzhou Breast Cancer Study (GZBCS) cohort with full consideration of the potential confounders and the modification effects. The results were further validated in the TCGA-BRCA cohort and explained by tumor immunity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
3
0
0
Order By: Relevance
“…The poor prognostic effect is observed in advanced (Stage 3) disease, and is present in HER-2 positive and triple negative breast cancers. Our data agrees with previous recent studies showing an association of high ENO1 expression with the aggressive basal subtype and a favourable prognosis in patients with early stage breast cancer but not with advanced stage disease and/or basal breast cancer [16,26,38]. We also observed that methylation of the gene is associated with a good prognostic effect, consistent with the expected effect from reducing ENO1 gene expression.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The poor prognostic effect is observed in advanced (Stage 3) disease, and is present in HER-2 positive and triple negative breast cancers. Our data agrees with previous recent studies showing an association of high ENO1 expression with the aggressive basal subtype and a favourable prognosis in patients with early stage breast cancer but not with advanced stage disease and/or basal breast cancer [16,26,38]. We also observed that methylation of the gene is associated with a good prognostic effect, consistent with the expected effect from reducing ENO1 gene expression.…”
Section: Discussionsupporting
confidence: 93%
“…A complex relationship of ENO1 with immune pathways was revealed by this study to complement other studies evaluating the role of ENO1 in the tumour-immune microenvironment [13,38,39]. Underexpression occurs in good prognostic subtypes of breast carcinoma, whereas overexpression of the pathways occurs in triple negative breast carcinomas.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation